Konsistensi Peraturan Daerah Kabupaten Bombana Nomor 1 Tahun 2019 Tentang Bantuan Hukum Untuk Masyarakat Miskin - Zulham Mubaraq; Muh. Asrianto Zainal (Institut Agama Islam (IAIN) Kendari, 2021)
This study aims to find out the Consistency of Local Regulation No. 1 of 2019 on Legal Aid for The Poor in Bombana District.Materials obtained from the results of interviews conducted in the field. The methods of collecting materials used in this study are, interviews, documentation and literature.The methods of material analysis used in this study are material reduction, material display, and material verification.Based on the results of the research conducted shows that the Regional Regulation Contingency No.1 year 2019 on Legal Aid for The Poor in Bombana District is still not running due to several factors, namely: Budgeting Factors, Factors in the absence of Legal Aid Institutions (LBH), Data collection of the poor to be assisted and Differences of Understanding and Opinion (Misuderstanding).So as to optimize the implementation of the government of Bombana Regency to make efforts, namely: Budget Proposal Implementation, socialization and verification of data of the poor, cooperation with the Legal Aid Institute (LBH) and community communication services (YANKOMAS). Researchers provide several recommendations, namely: For local governments to budget funds for the implementation of local regulations, for local governments to cooperate with legal aid agencies, to immediately verify and socialize related to the updated Social Welfare Data (DTKS) of the poor and so that local governments do not occur any more differences of understanding and opinion (misunderstanding)